Czech expatriates in China - the factors of success - Mudra, Tomáš; Lukeš, Martin, 1976-; Xiaokun, Li; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
Contributing to the available literature on the cross-cultural management between China and the Czech Republic, this thesis is examining the factors influencing the performance and success of Czechs working and living in China. It firstly defines the cultural settings of China and the Czech Republic, their key aspects and cultural specifics. Secondly, it describes the desired qualities of a successful expatriate - the so called global mindset. Thirdly, the thesis focuses on the specifics of working in China and on the potential culture shock a Czech expatriate is likely to face after relocating there. In the practical part of the thesis, the methods and results of an original primary field research conducted among more than 30 Czech expatriates in China are outlined. Using correlations and content analysis, the final results are drawn and the prior hypotheses either confirmed or disproved. The summary of the thesis offers then a set of recommendations for an expatriate-to-be who is coming to China - an ancient land surrounded by mysteries even in our modern times.
Vedoucí práce: Martin Lukeš
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses